When voice and self diverge: Voice incongruence as a marker of expressive writing dynamics - Moura, M.; Zeferino, I.; Jacques, T.; Moleiro, C.; Martins, M. (18th Congress of the European Federation of Sexology, 2026)
Objective: In this study, we examined differences in voice experience, including voice incongruence and health, across transgender and cisgender individuals, considering both identity (cis vs. trans) and gender (women vs. men), as well as voice dysphoria in transgender men and women. We further explored whether transgender women constitute a distinct group with respect to voice experience and tested whether voice experience is associated with expressive writing dynamics beyond identity and gender. Design and Method: Seventy-five participants took part in this study (M age = 24.39 ± 5.87 years): 20 transgender women, 16 transgender men, 20 cisgender women, and 19 cisgender men. Participants were recruited through clinical and community-based channels. Inclusion criteria were age between 18 and 45 years and native European Portuguese proficiency. Measures included questionnaires assessing sociodemographic, health, cognitive, and voice experience variables, and an expressive writing task focused on voice experience. Results: Transgender and cisgender participants differed in voice incongruence and health (ps < .001), and gender differences emerged only for voice incongruence (p < .001). A significant identity by gender interaction was found (p < .001). Planned contrasts showed that transgender women reported significantly higher voice incongruence than all other groups, as well as when compared specifically to cisgender women and transgender men (ps < .001). Within the transgender group, women reported higher voice dysphoria than men (p = .003). Writing dynamics varied as a function of voice incongruence: higher incongruence was associated with longer pauses (p = .025) and overall writing time (p = .042). No effects of identity or gender, nor their interaction, were found for writing dynamics. Conclusions: Voice incongruence emerges as a key experiential dimension distinguishing groups, particularly transgender women, and is reflected in the temporal organization of expressive writing. Writing behavior reflects subjective voice experience rather than categorical identity or gender alone.